INCOME SMOOTHING ANALYSIS IN THE COMPANY (CASE STUDY AT PT. KALBE FARMA. TBK YEAR 2017-2019) - Irvan Yoga Pardistya (STKIP Singkawang, 2020)
Profit is a goal orientation in the company's operations. For this reason, the performance of a company can be measured from the profits it gets. Income smoothing, in another case, is one of the methods used in distributing variations in profit achievement in a company's financial statements. This research, intends to describe the income smooting that has been achieved by PT. Kimia Farma Tbk. The research object is PT. Kimia Farma Tbk. Then, the unit of analysis is the company's financial statements for 2017-2019. Furthermore, the analysis technique uses quantitative descriptive. The results of the analysis explain that the company's Income smoothing is fluctuating. This can be seen from the increase in income smoothing in 2017 to 2018 which has increased, but 2018 to 2019 has decreased.